KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PT. SARANA BHAKTI TIMUR SURABAYA - Rini Wahyuni; Indriana Kristiawati (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
The purpose of this study was to determine Service Quality and Trust in Customer Loyalty PT. Sarana Bhakti Timur Surabaya. The population in this study is the service user of PT. Sarana Bhakti Timur, numbering 106 customers. Samples taken were 52 people. used as respondents in this study. Data analysis method used is multiple linear regression analysis, validity test and reliability test, using classical assumption deviation test and hypothesis testing. Based on the analysis and discussion, it can be concluded that the variable quality of service (X1) had a significant relationship on customer loyalty (Y) with t count equal to 5.668 is greater than t table of 2.00958, stating that the hypothesis to-1 in this research is proven true or can be accepted. With a significance level smaller than 0.05, the customer trust variable(X2) has a significant relationship to customer loyalty (Y) with tcount 2.485 greater than t table of 2.00958, with a significance level of less than 0.05, and service quality(X1) as well as customer trust (X2) together (simultaneously) has a significant relationship to the dependent variable, namely customer loyalty (Y), which means that overall service quality and customer trust variables have a relationship to customer loyalty variables so the hypothesis the second in this study proved the truth.